Noble Paganism. Orientalist Discourse on Tibetan Buddhism in Nineteenth-Century Russian Polemic Literature - Tsyrempilov, Nikolay (Inner Asia, 2016)
Tibetan Buddhism, in the eyes of Orthodox Christian polemicists, was always seen as a harmful paganism, and fifighting against this ‘superstition’ was a high priority. Based on analysis of nineteenth-century Russian Orthodox missionary articles, this paper examines the stereotyped portrayal of Tibetan Buddhism as a civilisational opponent to Christianity, and the ways Russian scholars, ethnographers, philosophers, and offiffcials either supported or challenged this view. In this paper, I argue that, in Russia, the Orientalist paradigm is common to a greater degree among Christian clergy than in academic circles due to the status of a dominating religion the Orthodoxу enjoyed in Russia. The Russian missionaries’ support of imperial power was the essential fac-tor. The clerics viewed themselves as carriers not only of Christian values, but also of the idea of Russian statehood and European civilisation in general. Russian Christian intellectuals repeatedly attempted to comprehend Buddhism rationally, but these attempts were highly formalistic. For them, academic study was never an end in itself, but, I argue, a convenient tool to achieve ideological domination and establish moral authority. However, their intellectual and psychological inability to view other reli-gions as different, rather than false, was, and still is, an obstacle to mutual understand-ing and respect between Christianity and Buddhism in today’s Russia.
Keywords: Buddhism; Orthodox Christianity; Russian empire; Buriats; Tibet; Mongolia